Towards a low-carbon society: spatial distribution, characteristics and implications of digital economy and carbon emissions decoupling - Yanan Wu; Zinb Abduljabbar Mohamed Al-Duais; Biyu Peng (Humanities & Social Sciences Communications, 2023)
Abstract Reducing carbon emissions and attaining sustainable economic, social, and environmental development are vital components of the 2030 Agenda for Sustainable Development. Previous research has overlooked the influence of the digital economy on urban carbon decoupling. To bridge this gap, this study employs GIS software and econometric models for analyzing the spatial distribution and characteristics of the digital economy and carbon decoupling and also investigates the direct, heterogeneous, and spatial effects of the digital economy on carbon decoupling. This study reveals: (1) A lesser digital economy presence in the northeast and northwest, while more developed in the Southeast Coast and municipalities directly under the Central Government. Cities with weak carbon decoupling are concentrated in Northeast and North China. (2) The digital economy and the decoupling of urban carbon emissions have spatial correlation and agglomeration characteristics. (3) The digital economy can contribute to decoupling carbon emissions in cities. (4) Improved urban carbon decoupling by the digital economy in central, eastern, and non-resource-based cities. (5) Spatial spillover effect in urban carbon emissions decoupling, yet the digital economy worsens nearby cities’ carbon decoupling due to a siphon effect. That research indicates that the digital economy holds significant promise not only in advancing human progress, bridging the digital divide, and fostering social development but also in driving the decoupling of urban carbon emissions.